Comprehensive abiotic taphonomic examination of stage 0 and 1 on Homiphoca (PHOCID, SEAL) long-bones, West Coast Fossil Park, South Africa - Doughty, Myra Beth (Stellenbosch : Stellenbosch University, 2021)
Thesis (MSc)--Stellenbosch University, 2021.